Exploring the link between Public Investment and Long Run Economic Growth: A Case of a Developing Country - Rawat, Amna Sohail; Khan, Lubna (Public Finance Quarterly, 2020)
This paper attempts to investigate the effect of public investment on the economic growth of Pakistan using an annual data series from the period of 1973-2015. An autoregressive distributed lag (ARDL) model is used to estimate the relationship between variables. Moreover, causality analysis and variance decomposition analysis have also been applied. The result of ARDL bound testing confirms the long run association between public investment and economic growth in Pakistan. In addition, the long run and short run estimations reveal that a large amount of public investment reduces the economic growth. However, the larger share of private investment enhances the economic growth. Conversely, an increase in the labor force of Pakistan will decrease the economic growth in the long run. The study evidence presents important policy implications for the government and policy makers to increase economic growth.